Left Ventricular Non-Compaction Revealed by a Sinus Node Dysfunction: Case Report and Literature Review - Louizi, W.; Belhoussine, H.; Doghmi, N.; Cherti, M. (RA Journal of Applied Research, 2021)
Left-ventricular non-compaction is a myocardial disease of the left ventricle, characterized by excessive trabeculations. The diagnosis relies is based on echocardiography and cardiac magnetic resonance imaging. We report a case of a 23-years-old patient diagnosed for left ventricular non compaction revealed by a sinus node dysfunction. This case underlines the importance of using multimodality imaging approach to enable a quick diagnosis which can be followed by appropriate treatment.